Explaining rebel-state collaboration in insurgency: keep your friends close but your enemies closer. (17th November 2021) - Schievels, Jelte Johannes; Colley, Thomas
ABSTRACT: Insurgencies are routinely conceptualised using a binary opposition between states and rebels. However, this neglects the complexity of their interaction, especially their collaboration. Although rebel-state collaboration is found throughout the history of insurgency, we lack a full explanation of why it occurs. This article endeavours to take the first step in developing a comprehensive theory by analysing rebel-state collaboration in two heuristic case studies: Afghanistan and Syria. Through process tracing, we find four mechanisms that can explain collaboration: 1) to prevent a costly military stalemate, 2) to gain or maintain legitimacy, 3) because external threats incentivise a mutually beneficial alliance, and 4) because both have to operate under the constraints of the pre-existing political economy. The relative weight of each varies, reflecting the fluid and contextual nature of wartime political orders. Contrasting with more popular explanations, we argue rebels and states are willing to collaborate even when the other benefits too, providing they believe their relative gains would be higher than their opponents, or the costs of competing would be too large. In providing a fuller explanation of rebel-state collaboration, we advocate a rethink about how to capture and analyse the complex and dynamic interactions between rebels and states.